Bridging theory and practice: Implementation of hybrid motorcycle prototypes as learning media in vocational automotive education - Ramdhani Ramdhani; Ridwan Adam M. Noor; Sriyono Sriyono; Nabiel Jabbar Fal; Wahid Munawar; Muhamad Maris Al Gifari (Universitas Negeri Padang, 2025)
Rapid advancements in hybrid vehicle technology demand significant adjustments in vocational education to equip students with relevant competencies. This study investigates the effectiveness of a hybrid motorcycle prototype as an innovative learning media to improve student learning outcomes in vocational automotive education. Employing a pre-experimental one-group pretest-post-test design, the research involved 30 Grade XI Automotive Engineering students at SMK Negeri 1 Cisarua. Participants underwent a pretest, followed by four prototype-based learning sessions, and a post-test. Data were analysed using descriptive statistics, paired-samples t-test, and normalized gain (g). Results demonstrated a substantial improvement in learning outcomes, with the mean score increasing from 58.5 to 82.67 (mean gain = 24.17 points; t(29) = 8.805, p < 0.001; Cohen's d = 1.61), indicating a very large effect size. The normalized gain of 0.55 suggests medium effectiveness based on Hake's classification. Furthermore, 90.0% (27/30) of students achieved scores ≥75 post-intervention, compared to 23.3% (7/30) beforehand. Aligning with Edgar Dale’s Cone of Experience, these findings highlight that direct, hands-on engagement enhances comprehension and retention. The study concludes that hybrid motorcycle prototypes offer a cost-effective, practical, and scalable solution to bridge the theory-practice gap in vocational automotive education, especially in motorcycle-dominant contexts. Recommendations include integrating prototype-based learning into the Merdeka Curriculum and expanding its application to other technical domains.